Morphological assessment of angiogenesis factor expression in tumor and microenvironment of breast fibroadenoma and ductal carcinoma: An observational cohort study - K. A. Aliyev; E. R. Asanova; T. P. Makalish; E. Yu. Zyablitskaya (Кубанский научный медицинский вестник, 2024)
Background. Angiogenesis plays a crucial role in the progression of breast cancer. Identifying and investigating the key components of this process, focused on phenotype as well as microenvironment of the tumor, is considered highly relevant for understanding tumor biology. Studies into the expression of angiogenesis-related factors by means of immunohistochemical methods appear valuable for both assessing conventional chemotherapy options and identifying new targets in targeted therapy for breast cancer. Objectives. To investigate angiogenesis in breast ductal carcinoma by assessing the expression of vascular endothelial growth factor, angiopoietin-2, and hypoxia-inducible factor alpha in the context of various therapeutic strategies. Methods. An observational cohort study was conducted using biopsy samples from female patients with confirmed diagnoses of “fibroadenoma” and “ductal carcinoma of the breast,” residents of the Republic of Crimea, who applied to oncological hospitals in Simferopol from January 2021 to January 2023. Examination involved histological sections of breast tumor tissue from 68 patients with verified diagnoses of “ductal carcinoma” and “fibroadenoma” (the mean age of the patients was 65 ± 5). The following cohorts were formed in the study: control group, consisting of patients with breast fibroadenoma (n = 20); two subgroups of patients with ductal carcinoma of the breast (n = 48), including Group I — patients with ductal carcinoma of the breast who had not received chemotherapy (n = 23), Group II — patients with ductal carcinoma of the breast, who underwent surgery following one or more courses of chemotherapy (n = 25). The study involved examining the tumor tissue sections obtained from paraffin blocks, assessing the expression of angiogenesis markers via immunohistochemistry using primary antibodies against vascular endothelial growth factor, angiopoietin 2, and hypoxia-inducible factor alpha. Statistical analysis was carried out using Statistica 10.0 (StatSoft, USA). Differences were considered significant at error probability p ≤ 0.05. The value of p < 0.05 was deemed statistically significant for all types of analysis. Results. The expression of hypoxia-inducible and vascular growth factors differed significantly between both groups with breast ductal carcinoma as well as when compared to the control group. The hypoxia-inducible factor having cytoplasmic localization was detected in the control group with benign processes, whereas the nuclear expression was noted in the breast ductal carcinoma groups. Significant differences in the nuclear expression of hypoxia-inducible factor have been established among groups of patients with confirmed ductal carcinoma of the breast: in Group II, which underwent chemotherapy, expression was notably higher in both the tumor stroma and in the stroma of tumor-free areas. The hypoxia-inducible factor expression was significantly greater at the demarcation zone than that observed in samples from surgically treated women in Group I (p = 0.033; p = 0.034, p < 0.001, respectively). In the tumor epithelium of patients with breast ductal carcinoma, vascular endothelial growth factor was expressed significantly more intensively in the group who did not receive chemotherapy compared to the other group (p < 0.001). Conversely, in the tumor stroma, angiopoietin exhibited significantly higher expression levels among patients who underwent chemotherapy compared to those who received no treatment; this was observed in both the tumor areas due to endothelial cell involvement (p = 0.004) and in conditionally healthy regions of the breast (p < 0.001). In the control group represented by fibroadenoma patients, the expression of the studied factors is more pronounced than in the groups with ductal carcinoma of the breast. Conclusion. The obtained data indicate the activation of angiogenesis processes in the group of patients after chemotherapy, as evidenced by the increased expression of hypoxia-inducible factor, vascular endothelial growth factor, and angiopoietin. This result is associated with the high prevalence of resistant forms of breast ductal carcinoma in Group II. The study of the signaling pathways of angiogenesis and its components provides valuable insights into patterns of occurrence and strategies to overcome chemotherapy resistance in ductal carcinoma of the breast.